Analisis Hak Pesangon Pekerja PHK Berdasarkan Perspektif Omnibus Law dan Pasal 156 Perppu Nomor 2 Tahun 2022 Tentang Cipta Kerja - Izzati, Aulia Putri; S, Suwarsit (Media Hukum Indonesia (MHI), 2024)
The aim of this research is to analyze the implementation of severance pay rights for employees affected by layoffs based on Article 156 of Government Regulation in Lieu of Law Number 2 of 2022 (Peru) concerning the Manufacturing Industry. This Perppu plays an important role in regulating the rights and protection of workers affected by layoffs in Indonesia. This study uses normative law based on Perppu Number 2 of 2022 concerning Job Creation, and its compliance with related laws and regulations has been reassessed. Data collection was carried out through a literature review of articles, books and related laws and regulations. The report's findings show that the implementation of severance pay rights for workers affected by layoffs based on Article 156 of Presidential Decree No. 2 of 2022 is still weak and many employers do not fulfill their obligations based on this article. In conclusion, the implementation of the obligation to pay severance pay to workers affected by layoffs based on Article 156 of Perppu Number 2 of 2022 has important implications in ensuring the protection of workers who lose their jobs in a legal system.